Application of systematic methods in the electromechanical design of an agricultural mobile robot - Tabile, Rubens Andre; Godoy, Eduardo Paciencia [UNESP]; Tangerino, Giovana Tripoloni; Porto, Arthur José Vieira; Inamasu, Ricardo Yassushi; De Sousa, Rafael Vieira (Elsevier, 2013)
A current trend in the agricultural area is the development of mobile robots and autonomous vehicles for precision agriculture. One of the major challenges in the design of these robots is the development of the electromechanical components. This platform has as main characteristics four-wheel propulsion and independent steering, adjustable gauge, ground clearance of 1.80 m, diesel engine, hydraulic system, and a CAN-based networked control system. The aim of this work is to describe the project of an experimental platform for data acquisition in field for the study of the spatial variability and development of agricultural robotics technologies to operate in agricultural environments. This proposal is based on a description of the design process and definition of the design parameters utilized. Copyright © 2013 IFAC.
Keywords: Agricultural machines; Mechanical design; Precision agriculture